Family physician remuneration schemes and specialist referrals: Quasi‐experimental evidence from Ontario, Canada. (26th June 2018) - Sarma, Sisira; Mehta, Nirav; Devlin, Rose Anne; Kpelitse, Koffi Ahoto; Li, Lihua
Abstract: Understanding how family physicians respond to incentives from remuneration schemes is a central theme in the literature. One understudied aspect is referrals to specialists. Although the theoretical literature has suggested that capitation increases referrals to specialists, the empirical evidence is mixed. We push forward the empirical research on this question by studying family physicians who switched from blended fee‐for‐service to blended capitation in Ontario, Canada. Using several health administrative databases from 2005 to 2013, we rely on inverse probability weighting with fixed‐effects regression models to account for observed and unobserved differences between the switchers and nonswitchers. Switching from blended fee‐for‐service to blended capitation increases referrals to specialists by about 5% to 7% per annum. The cost of specialist referrals is about 7 to 9% higher in the blended capitation model relative to the blended fee‐for‐service. These results are generally robust to a variety of alternative model specifications and matching techniques, suggesting that they are driven partly by the incentive effect of remuneration. Policy makers need to consider the benefits of capitation payment scheme against the unintended consequences of higher referrals to specialists.